The centrality of agriculture : between humankind and the rest of nature - Duncan, Colin A. M. (Colin Adrien MacKinley), 1954- (McGill-Queen's University Press, 1996)
Using ecological, historical, humanist, institutionalist, and Marxist methodologies, Colin Duncan argues that the entire project of developing the theory of political economy has been seriously sidetracked by industrialism. Using England as a case study he shows that the relationship between modernity and agriculture need not be so uncomfortable and suggests ways in which the original socialist project can be rejuvenated to make it both more feasible and more attractive. Duncan concludes that no sustainable human future can be conceived unless and until the centrality of agriculture is properly recognized and new economic institutions are developed that will encourage people to take care of their landscapes.